EMPLOYEE PERFORMANCE IN IMPROVING THE QUALITY OF SERVICE FOR INPATIENT BPJS PATIENTS AT PERMATA HATI DURI HOSPITAL, BENGKALIS DISTRICT - Oky Sarita Putri; Sitti Rahmah (Yayasan Wayan Marwan Pulungan, 2024)
The research method and location of this research was carried out at Permata Hati Duri Hospital, Bengkalis Regency. The research location and location was chosen for the reason that the researcher wanted to know employee performance. This type of qualitative research with data sources consisting of primary data and secondary data. The research informants consisted of doctors on duty, nurses on duty, nurses, security and the community. Data collection techniques used observation and interview guidelines. Data analysis techniques include data reduction, data presentation and verification. The results of the research found that employees were not said to be good because there were still complaints regarding the employees' ability to carry out their work to draw blood from patients, the community asked that employees be placed according to their respective abilities, the employees' skills in carrying out the tasks given were quite good. Employees have carried out their performance in quantity by providing various services and completing their duties and responsibilities on time. The punctuality of hospital employees is not good enough in completing their work, the alertness of employees is still delayed in responding, waiting for nurses for hours. The registration queue is quite long. Employees provide poor treatment, are indifferent, speak in a bad tone and are cynical to patients/patients' families. Employee independence is quite good and they are responsible for the tasks given.